Knowledge sharing behavior model among librarian in Northern Peninsular Malaysia / Mohd Zool Hilmie Mohamed Sawal…[et al.] - Mohamed Sawal, Mohd Zool Hilmie; Raja Omar, Raja Alwi; Noordin, Nazni; Abdul Rahman, Abd Latif; Zakaria, Zaherawati (Research Management Institude, 2015)
While studies investigating knowledge sharing behaviors have been extensively reported in the Information Systems and Library Science literature, very few have attempted to explore the role of Big Five Personality Factors and Subjective Norm on knowledge Sharing Behaviors among librarians. In particular, studies focusing on Malaysian librarians are still very scarce. This study examines the factors influencing the Knowledge Sharing Behavior among librarians in Northern Peninsular Malaysia and to formulate a new model of Knowledge Sharing Behavior among librarian from Big Five Personality Factors and Subjective Norm perspective. This study will adopt survey method and expected to increase understanding towards Big Five Personality factors and Subjective Norm as determinants of knowledge sharing behavior among Northern Peninsular Malaysian librarians. The data will be analyzed using Partial Least Square (PLS) technique using SmartPLS. The result from this study is expected to increase understanding and assist librarians and information professionals as the information providers with the development of another new model for Knowledge Sharing Behavior according to the Big Five Personality and Subjective Norm perspectives